2020
DOI: 10.1108/ijshe-10-2019-0320
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perceptions of HEI regarding environmental sustainability – a comparative analysis

Abstract: Purpose This paper aims to compare the environmental sustainability practices at the campus operations between two Portuguese higher education institutions (HEIs) at different stages of the implementation of an Eco-School Programme. It also seeks to analyse the involvement of the students in the process of implementing these practices in their institutions. Design/methodology/approach A questionnaire survey was carried out in two HEIs (a green and a non-green institution). Data were collected from a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
2
8
0
2
Order By: Relevance
“…The students expressed their awareness and interest in university's campaigns regarding sustainability, but it is surprising that despite knowing about these communication activities and preferring them as sources of information on sustainability, they seldom participated in them. This also supported the findings of Correia et al (2020) as they stressed that more communication programs and efforts should be done toward sustainability such as workshops, initiatives and campaigns. In both awareness level and teaching methods level, Finnveden et al (2020) and Nikolic et al (2020) found that it is necessary to include the knowledge, values and practice skills in sustainable university programs.…”
Section: Discussionsupporting
confidence: 79%
“…The students expressed their awareness and interest in university's campaigns regarding sustainability, but it is surprising that despite knowing about these communication activities and preferring them as sources of information on sustainability, they seldom participated in them. This also supported the findings of Correia et al (2020) as they stressed that more communication programs and efforts should be done toward sustainability such as workshops, initiatives and campaigns. In both awareness level and teaching methods level, Finnveden et al (2020) and Nikolic et al (2020) found that it is necessary to include the knowledge, values and practice skills in sustainable university programs.…”
Section: Discussionsupporting
confidence: 79%
“…Further, Migliorini et al (2020) investigated the level of knowledge of students regarding sustainable food systems, Alsaati et al (2020) and Edumadze et al (2014) explored awareness on sustainable development and environmental impacts of electronic wastes, respectively, in students. Correia et al (2020) and Gazzola et al (2020) focused on the perceptions of students regarding campus sustainable practices and the circularity of the fashion industry, respectively. In general, each paper analyzed the behavior of students using descriptive statistics.…”
Section: Resultsmentioning
confidence: 99%
“…The Wilcoxon-Mann-Whitney test is used to compare two independent samples when the data are interval scaled but the assumptions for the t-test (normality) are not satisfied; when ordinal (ranked) scales are used to compare two independent samples because the data are interval scaled but the assumptions for the t-test (normality) are not satisfied; or when ordinal (ranked) scales are used because the data are not normally distributed ( Jakobsson, 2004 ; McCrum-Gardner, 2008 ). Several research studies in higher education have used this test to compare the central tendency of a variable of interest in two groups (e.g., Dabic et al., 2012 ; Correia et al., 2020 ). To compare perceptions between students with high and low-medium use of social media sites, the levels of frequency of exposure to messages on social media were defined in two categories: from never to 2 or 3 times per week (levels 1 to 5) reflecting low-medium frequency, and daily or more than one time per day representing high frequency (levels 7 and 8).…”
Section: Methodsmentioning
confidence: 99%